The Role of Migrant Stock and Lagged Migration in the Settlement Patterns of Nineteenth Century Immigrants - Dunlevy, James A.; Gemery, Henry A. (The Review of Economics and Statistics, 1977)
James A. Dunlevy, Henry A. Gemery, The Role of Migrant Stock and Lagged Migration in the Settlement Patterns of Nineteenth Century Immigrants, The Review of Economics and Statistics, Vol. 59, No. 2 (May, 1977), pp. 137-144